Geriatric factors affecting the safety of direct oral anticoagulants in atrial fibrillation patients aged 80 years and older: An observational prospective cohort study - M. S. Cherniaeva; A. O. Pavlova; P. A. Alferova; M. A. Rozhkova; M. I. Trifonov; T. V. Nikeeva; L. A. Egorova; O. M. Maslennikova; N. V. Lomakin; D. A. Sychev (Кубанский научный медицинский вестник, 2025)
Background. Older age is associated with the presence of geriatric syndromes, whose effect on the safety of direct oral anticoagulants in atrial fibrillation patients is studied extensively. Scientific literature focuses on the prevention of major bleeding, while clinically relevant non-major bleeding occurs much more frequently and can have a significant impact on the patient’s condition. Objective. To assess the potential of geriatric factors for predicting the risk of clinically relevant non-major bleeding on direct oral anticoagulants in nonvalvular atrial fibrillation patients aged 80 years and older. Methods. The article presents the results of an observational prospective cohort study that included 367 atrial fibrillation patients aged 80 years and older on direct oral anticoagulants. The study was conducted at a multi-specialty inpatient clinic in Moscow from January 2019 to December 2022 and reflected real clinical practice. The medical records were prospectively analyzed for the presence of clinically relevant non-major bleeding; the observation period lasted 12 months. The patients were divided into groups: the main group comprising patients with clinically relevant non-major bleeding (n = 195), with a median age of 84 [82; 87] years, and the control group consisting of patients without clinically relevant non-major bleeding (n = 172), with a median age of 84 [82; 88] years. The groups were comparable in terms of key bleeding risk factors. In order to identify geriatric risk factors, a comprehensive geriatric assessment was performed in four main domains: physical status; mental and emotional status; functional capacity; identification of social problems. Statistical data processing and visualization were performed in the R software environment, version 4.4.0 (R Foundation for Statistical Computing, Vienna, Austria). Differences were considered statistically significant at p < 0.05. Results. The performed analysis identified risk factors for clinically relevant non-major bleeding in all four domains of the comprehensive geriatric assessment: social (living in a family, number of household members, legal marriage, and church attendance); mental and emotional (Geriatric Depression Scale); physical and functional (balance tests, Lawton IADL scale, use of assistive devices, senile asthenia as per the Age is No Barrier questionnaire, SPRINT (Systolic Blood Pressure Intervention Trial) frailty index, p < 0.05). In the course of a multiple-factor analysis, a multiple-factor logistic regression model was created to predict clinically relevant non-major bleeding, and a prognostic nomogram was derived to estimate the probability of clinically relevant non-major bleeding (prognostic accuracy of 59.9%, sensitivity of 48.9%, and specificity of 72.4%). The predictors were as follows: number of household members, Barthel ADL score, Lawton IADL score, Timed Up and Go Test, and use of any assistive device. Conclusion. In the study, socially active, emotionally stable, mobile, and robust patients were shown to have a higher risk of developing clinically relevant non-major bleeding events. The authors identified geriatric factors that may serve as predictors of clinically relevant non-major bleeding on direct oral anticoagulants in atrial fibrillation patients aged over 80 years. Given the active AI implementation in clinical practice, the obtained data can be integrated into clinical decision support systems.